Aspilia africana (Pers.) C.D. Adams and Manihot esculenta Crantz Exhibit Antibacterial Activity against Resistant Salmonella typhi Strains - Richard Agyen; Yaw Duah Boakye; Theresa Appiah Agana; Vivian Etsiapa Boamah; Clement Osei Akoto; Michael Owusu; Francis Adu; Christian Agyare (Scientifica)
Typhoid fever, caused by Salmonella typhi, has plagued underdeveloped countries for many years. Recently, there has been a surge in S. typhi strains identified to be multidrug-resistant in endemic areas. Aspilia africana and Manihot esculenta have been reported to exhibit activity against S. typhi; however, this study aimed to investigate the effect of A. africana and M. esculenta against resistance strains of S. typhi. The leaves of the plants were extracted using distilled water (hot (AQH) and cold (AQC)), methanol (MET), ethyl acetate, and petroleum ether. The extracts were screened in vitro for anti-Salmonella effects against fourteen S. typhi isolates (five multidrug-resistant (MDRST), five ciprofloxacin-resistant (CRST), three nalidixic acid-resistant (NARST), and one sensitive isolate (SS)) using agar well diffusion and microbroth dilution methods. Phytochemical screening showed the presence of tannins, saponins, glycosides, and flavonoids in all polar solvent extracts. Alkaloids were found in all extracts, while triterpenoids were present in all except the aqueous extracts. The AQC of A. africana had the best inhibitory effect on the MDRST and NARST with diameter zones of inhibitions (DZOIs) of 40.0 ± 2.08 mm and 34.0 ± 3.22 mm, respectively. Methanol extract of A. africana had the best inhibitory effect on CRST and SS with DZOIs of 34.0 ± 2.08 and 43.0 ± 3.06 mm, respectively. The AQC and AQH of A. africana and AQH of M. esculenta produced the best MICs and MBCs of 2.5 and 5.0 mg/mL against the MDRST. There was no significant difference in ZOIs of the different solvent extracts against test organisms at p<0.05. Gas chromatography-mass spectrometry analysis of the extracts showed compounds such as n-hexadecanoic acid, 9,12,15-octadecatrienoic acid (9.55%), and 2H-benzo[F]oxireno[2,3-E]benzofuran-8(9H)-one in the A. Africana extracts and D-mannose, 3-nitrophenyl, methanol acetate (ester), and 9-octadecenamide in the M. esculenta extracts. The leaves of M. esculenta and A. Africana are effective against multidrug-resistant Salmonella isolates.